2007
DOI: 10.1515/cclm.2007.018
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of homocysteine, neopterin and nitric oxide levels in Behcet's disease

Abstract: In contrast to recurrent aphthous stomatitis, there is a higher prevalence of hyperhomocysteinemia in Behcet's disease. Homocysteine may have deleterious effects on the pathology of Behcet's disease by decreasing nitric oxide levels and interfering with the immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 41 publications
2
25
1
Order By: Relevance
“…Gunduz et al (29) reported no significant change in plasma NO levels in RAU and Behcet's disease. Ozkan et al (30) reported no significant difference between the serum NO levels in RAU and healthy patients, but reported a significant difference among patients with Behcet's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Gunduz et al (29) reported no significant change in plasma NO levels in RAU and Behcet's disease. Ozkan et al (30) reported no significant difference between the serum NO levels in RAU and healthy patients, but reported a significant difference among patients with Behcet's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Homocysteine was reported to be higher in patients with BS, particularly in patients with active disease status compared to healthy controls. 16,17 Elevated Hcy has also been reported to be associated with thrombosis in vascular BS in several studies. [18][19][20][21] Cerebral venous sinus thrombosis frequently co-occurs with peripheral venous vascular events such as deep venous thrombosis and pulmonary vascular disease; therefore, serum Hcy levels are expected to be high in vascular NBS.…”
Section: Discussionmentioning
confidence: 99%
“…77 In another recent study, hyperhomocysteinemia was confirmed as a definite finding in BD patients compared to controls. 96 Other researchers have found no association between venous involvement and hyperhomo-cysteinemia, thought not to be an independent factor for vascular involvement. 97 Aksu 93 hypothesized that homocysteine had a deleterious effect on endothelial cells, causing endothelial cell damage, smooth muscle cell proliferation, and increased oxidative stress.…”
Section: Homocysteinementioning
confidence: 95%
“…Homocysteine activates T cells and increases the interaction of monocytes and T cells with endothelial cells. 96 From these studies it is obvious that the exact mechanism by which hyperhomocysteinemia is related to vascular disease and venous thrombosis remains to be clarified by further investigation.…”
Section: Homocysteinementioning
confidence: 99%